Case report: Gastric langerhans cell histiocytosis with BRAF deletion mutation in a child that was misdiagnosed as lymphoma - Wan, Zhi; Tang, Xue; Gao, Ju; Sun, Jing-jing (Frontiers in Oncology, 2025)
Langerhans cell histiocytosis (LCH) is a myeloid neoplasm associated with the infiltration of most organs but rarely involves the stomach. Stomach tumors in children are very rare and can be easily misdiagnosed. We report the first case of gastric LCH in a 9-year-old boy who was misdiagnosed with gastric lymphoma. The patient presented to our outpatient department with recurrent abdominal pain that had lasted 1 month. Due to the absence of typical clinical features associated with lymphoma in the boy, the initial diagnosis of lymphoma based on the first gastric pathological biopsy was questioned. The second pathological examination revealed that the tumor cells expressed CD1a, S-100, and Langerin with BRAF (c.1457_1471del) deletion mutations. The patient’s condition rapidly improved after chemotherapy with prednisone and vincristine. This case report focuses on the possibility of gastric LCH in school-aged children and the differential diagnosis of gastric tumors in children.